2018
DOI: 10.26508/lsa.201800164
|View full text |Cite
|
Sign up to set email alerts
|

Absence of MHC-II expression by lymph node stromal cells results in autoimmunity

Abstract: MHCII-restricted antigen presentation by lymph node stromal cells is essential for regulatory T-cell proliferation and functions, and for the regulation of autoimmunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(68 citation statements)
references
References 42 publications
2
66
0
Order By: Relevance
“…This promoter is responsive to IFNγ and other pro-inflammatory cytokines, which induce MHC II expression/up-regulation in fibroblasts and BEC (6). Similarly, in LEC it has been shown that endogenous MHC II expression is controlled by CIITA IV (4, 5). However, it is interesting to notice that, in contrast to other non-professional APC where pro-inflammatory stimuli greatly up-regulate surface MHC II molecules, pro-inflammatory stimuli induce less robust MHC II up-regulation in LEC (3, 5, 7).…”
Section: Mhc I and Mhc Ii Antigen Processing Machinerymentioning
confidence: 94%
See 1 more Smart Citation
“…This promoter is responsive to IFNγ and other pro-inflammatory cytokines, which induce MHC II expression/up-regulation in fibroblasts and BEC (6). Similarly, in LEC it has been shown that endogenous MHC II expression is controlled by CIITA IV (4, 5). However, it is interesting to notice that, in contrast to other non-professional APC where pro-inflammatory stimuli greatly up-regulate surface MHC II molecules, pro-inflammatory stimuli induce less robust MHC II up-regulation in LEC (3, 5, 7).…”
Section: Mhc I and Mhc Ii Antigen Processing Machinerymentioning
confidence: 94%
“…The MHC II surface expression in LN-LEC is similar to what observed in BEC but less than fibroblastic reticular cells from LN (1). LEC MHC II molecules are both endogenously synthesized or acquired from hematopoietic cells, as determined by chimera experiments in MHC II −/− mice (1, 4, 5). At the transcription level, MHC II expression is regulated by CIITA, which is not a DNA binding factor but instead a transactivator that regulates quantitative aspects of MHC-II expression by binding the MHC-II enhanceosome (6).…”
Section: Mhc I and Mhc Ii Antigen Processing Machinerymentioning
confidence: 99%
“…Similarly, PD-L1 is upregulated in beta cells from humans with type 1 diabetes and NOD mice, in association with T cell infiltration and IFNγ production [34]. MHC-II expression on mouse LNSCs is low yet appears to be sufficient to affect autoreactive CD4 + T cells and contribute to the maintenance of regulatory T cells [35], and lack of MHC-II expression by LNSCs can result in autoimmunity in mice [36]. HLA-DR expression on human LNSCs is higher than in mice and, in the context of type 1 diabetes, was highly upregulated, along with PD-L1 to some extent.…”
Section: In S P T P R N G a D 2 G 6 P C 2 T Y R M L A N A T N F A Ipmentioning
confidence: 99%
“…In particular, LECs specifically induce CD4 + T cell death, whereas LECs, BECs and FRCs all induce T cell anergy (28). Moreover, our recent studies demonstrate that the loss of MHCII expression on LNSCs in murine LNs impairs peripheral CD4 + T cell tolerance, and alters regulatory T cell populations, resulting in signs of spontaneous autoimmunity in elderly (30). Their lack of costimulatory molecules could explain LNSC implication in T cell tolerance.…”
Section: Lymphatic Vessels As Immunoregulators In Non-tumor Contextmentioning
confidence: 99%